2019
DOI: 10.3389/fimmu.2019.02569
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Infection-Induced Thrombosis: Lessons Learned From Animal Models

Abstract: Thrombosis is a common consequence of infection that is associated with poor patient outcome. Nevertheless, the mechanisms by which infection-associated thrombosis is induced, maintained and resolved are poorly understood, as is the contribution thrombosis makes to host control of infection and pathogen spread. The key difference between infection-associated thrombosis and thrombosis in other circumstances is a stronger inflammation-mediated component caused by the presence of the pathogen and its products. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 151 publications
(194 reference statements)
3
132
0
5
Order By: Relevance
“…Many bacteria such as Helicobacter pylori, Chlamydia pneumoniae, Mycoplasma pneumoniae, Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aureus, Escherichia coli increase the risk associated with the stroke. 5 It has also been reported that various cardiovascular diseases may be associated with bacterial involvement as shown on the example of infective endocarditis. 108 Relationships between pneumonia due to Haemophilus influenzae and infection with other bacteria and myocardial infarction have been confirmed.…”
Section: Clinical Aspectsmentioning
confidence: 98%
See 3 more Smart Citations
“…Many bacteria such as Helicobacter pylori, Chlamydia pneumoniae, Mycoplasma pneumoniae, Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aureus, Escherichia coli increase the risk associated with the stroke. 5 It has also been reported that various cardiovascular diseases may be associated with bacterial involvement as shown on the example of infective endocarditis. 108 Relationships between pneumonia due to Haemophilus influenzae and infection with other bacteria and myocardial infarction have been confirmed.…”
Section: Clinical Aspectsmentioning
confidence: 98%
“…17 It is believed that systemic infections increase the risk of deep vein thrombosis/pulmonary embolism about 2-20 times. 5 An additional risk factor for VTE is the age of the patients, the presence of malignant tumors, and hereditary features. 3 It is also known that the formation of blood clots in vessels occurs during sepsis, which indicates the participation of bacteria in this process.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this and other animal models showed histological evidence of fibrin deposits in multiple organs such as the spleen, liver, lungs, and kidneys. 16,17 These fibrin deposits could be associated with activated macrophages, which in turn are attracted by infected cells, demonstrating the interplay between inflammatory cells and the advent of systemic coagulopathy. In another experiment, mice infected with influenza virus showed platelet aggregation, pulmonary microvascular thrombosis, endothelial dysfunction, and hyperinflammatory cytokine responses.…”
Section: Understanding Covid-19 Pathogenesismentioning
confidence: 99%